Intraspecific variations in life history traits of two pecky rice bug species from Japan: Mapping emergence dates and number of annual generations. Issue 23 (12th November 2021) - Yamasaki, Kazuhisa; Tabuchi, Ken; Takahashi, Akihiko; Osawa, Takeshi; Yoshioka, Akira; Ishigooka, Yasushi; Sudo, Shigeto; Takada, Mayura B.
Abstract: The mirid bugs Stenotus rubrovittatus and Trigonotylus caelestialium, which cause pecky rice, have become a threat to rice cultivation in Asia. Damage caused by these pests has rapidly become frequent since around 2000 in Japan. Their expansion pattern is not simple, and predicting their future spread remains challenging. Some insects with wide ranges have locally adapted variations in life‐history traits. We performed laboratory rearing experiments to assess the geographical scale of intraspecific variations in life‐history traits of S. rubrovittatus and T .  caelestialium . The experiments were aimed at increasing the accuracy of occurrence estimates and the number of generations per year. These results were compared with previous research, and differences in development rates were observed between populations of different latitudes, but not of the same latitude. Finally, plotting the timing of adult emergence and the potential number of generations per year on maps with a 5‐km grid revealed that they differed greatly locally at the same latitude. These maps can be used for developing more efficient methods of managing mirid bugs in integrated pest management. Abstract : Our laboratory rearing experiments revealed no difference in the relationship between temperature and the rate of development in each developmental stage of the two mirid bug species from the same latitude in northern Japan. On the other hand, comparison of data on the development rates in Tohoku region and those of previous studies in other areas revealed that the relationship between temperature and the rate of development showed geographical variations between populations of both species at different latitudes. We mapped the timing of adult emergence of the first generation and the potential number of generations per year using the daily mean temperature and our data on the two species' development in an effective accumulated temperatures model.